Conflict Resolution Education to Elementary School Learners Building Peace for Life - Chinara, Benudhar; Badakhshan, Kishwar (JOURNAL OF INDIAN EDUCATION, 2015)
Facing conflict is accepted and expected part of life and one cannot do anything to avoid it. Life in classroom, play field and school is not free of it. Teachers often complain that half of their classroom time is consumed in dealing with conflicts that their students face routinely, thereby inevitably ruining away the peace in the classrooms. It is a fact that a good experience learned at a young age is nevertheless forgotten. Breaking the conflict in the elementary classrooms is thus the first step in and an integral part of elementary classrooms to promote peace among young learners. The question is thus how? In this context, the paper identifies four common types of conflicts in elementary classrooms: touch-me-not, I am the boss, you love me / love me not, and I am the best. In continuation, it suggests four strategies such as role play, reflective listening, and dealing with feelings, and talks it out for resolving such conflicts among elementary school learners. Understanding the consequences of conflicts through the successful use of these strategies may empower the elementary learners with the skills of effective communication and emotional wellbeing which they can use in life outside the classrooms to build peace for life. This will ensure that they grow up into a responsible adult, thereby making a remarkable impact as positive agent of peace for a state of peaceful co-existence of all.